“The Big Book of Errors” (New Collected Works of Vladimir Narbut) - Vadim G. Besprozvanny (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
This review of the newly published book “Vladimir Narbut. Poetry. Translations. Prose” (Roman Kozhukharov, ed., Moscow, 2018) evaluates the textual criticism methods applied to this collection, reflects on the quality of the commentaries and the preface essay, and reveals a remarkable number of flaws the new edition has: the altered structure of the poetic cycles, chronological and bibliographical errors, and issues with text variants. The editor demonstrates little regard for the textual accuracy, and employs a self-contradictory strategy for the versions and drafts of the poetic texts. The commentaries that supply the book lack merely a professional approach: some are too detailed (or too telegraphic), others disconnect from the context, and some are irrelevant or misguided. The latter is particularly true for the Russian-Ukrainian interlingual homographs and homonyms, and ethnographic realia. The long-winded preface essay provides a detailed overview of the poet’s life, and is full of debatable esoteric assumptions and preposterous conclusions.